HIV-1 subtype B and C GP120-mediated apoptosis of bystander CD4+ T lymphocytes - Pillay, Natasha Camilla (My University, 2012)
Human Immunodeficiency Virus type 1 (HIV-1) is the causal agent of AIDS, and currently infects 33.3 million individuals worldwide. The gradual depletion of CD4+ T lymphocytes is a characteristic feature of a progressive HIV-1 infection. During HIV-1 infection the number of infected CD4+ T lymphocytes is fewer than the number of CD4+ T lymphocytes that are depleted, therefore suggesting a role for HIV-mediated apoptosis of uninfected bystander CD4+ T lymphocytes. Apoptosis, also known as programmed cell death, is a highly regulated, normal physiological process that results in the disposal of unwanted or corrupted cells such as virally infected cells. Several HIV-1 proteins are involved in HIV-1-mediated apoptosis, of which the envelope (Env) glycoprotein gp120 subunit is the most effective. However, the true mechanism of gp120-mediated apoptosis of uninfected CD4+ T lymphocytes is not fully understood and remains controversial. Furthermore, research focusing on HIV-1 subtype C Env-mediated apoptosis is limited. This study compared the ability of CCR5-utilizing soluble monomeric HIV-1 subtype C gp120 (gp120ZM651), monomeric HIV-1 subtype B gp120 (gp120BaL) and trimeric/oligomeric HIV-1 subtype C gp140 (gp140AncC) to induce apoptosis of uninfected Jurkat T lymphocytes and activated CD4+ T lymphocytes via CD4 and CD4/CCR5 signalling, respectively. All three Env glycoproteins were expressed in HEK 293T cells, purified by lectin affinity chromatography and characterized by assessing their binding capabilities to monoclonal antibodies IgGb12, 17b (in the presence and absence of soluble CD4) and 2G12. Purified recombinant gp120BaL, gp120ZM651 and gp140AncC were found to v be functional and conformationally intact and subsequently added in different concentrations to uninfected Jurkat T lymphocytes and activated CD4+ T lymphocytes. Apoptosis was detected by flow cytometry using Annexin V/7-AAD staining for up to 48 hours post treatment, and further confirmed by TUNEL analysis at 65 hours post treatment. Recombinant gp120BaL, gp120ZM651 and gp140AncC induced low levels of apoptosis in the Jurkat T lymphocytes (6.1%, 5.0% and 6.8%, respectively) and higher levels of apoptosis in the activated CD4+ T lymphocytes (13.3%, 15.6% and 11.5%, respectively) via TUNEL analysis of chromosomal DNA fragmentation. Moreover, comparable levels of apoptosis were observed between the monomeric gp120 and trimeric/oligomeric gp140 forms in both cell types. Interestingly, the subtype C gp140AncC induced higher levels of apoptosis than subtype C gp120ZM651 and subtype B gp120BaL in activated CD4+ T lymphocytes during the Annexin V/7-AAD analysis while the subtype C gp120ZM651 induced higher levels of apoptosis than subtype C gp140AncC and subtype B gp120BaL in activated CD4+ T lymphocytes during the TUNEL analysis. Overall, these results suggest that soluble gp120 is able to mediate low levels of apoptosis via CD4 signalling only in Jurkat T lymphocytes, and these levels are enhanced in activated CD4+ T lymphocytes, possibly due to engagement of gp120 with CD4 and the CCR5 co-receptor on the surface of the target cell.
M.Sc. (Med.), Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: HIV-1; Apoptosis